The Effect of Entrepreneurship Orientation and Marketing Innovations on Competitive Advantage and Their Impact on Business Performance of Small and Medium Culinary Business in DKI Jakarta during the Covid 19 Pandemic - Viniyati Maftuchach; Abdul Rohman; Ahmad Darda (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The development of the Indonesian economy, especially the micro, small and medium-sized businesses, especially the culinary industry is facing serious challenges due to the COVID-19 outbreak, this is due to the government's imposition of restrictions. DKI Jakarta as an economic center is still imposing strict restrictions on human movement. The impact is that most of the culinary MSME customers have disappeared, which in the end made most of the culinary MSME business actors out of business. However, in the midst of this crisis, there are still culinary MSME business actors who still survive, of course this needs to be disclosed so that it can be a lesson and input for policy makers and culinary MSME business actors themselves. The approach so that SMEs are able to turn challenges into opportunities that help them to survive is important. This study aims to analyze the effect of Entrepreneurship Orientation and Marketing Innovation on the Competitive Advantage of Culinary MSMEs in DKI Jakarta during the Covid 19 Pandemic and their impact on Business Performance. This study uses 100 selected respondents and the analysis method uses the Structural Equation Model (SEM) with the SmartPLS 3.0 analysis tool. The results of the study show that Entrepreneurship Orientation and Marketing Innovation have a significant effect on the Competitive Advantage of Culinary MSMEs in Jakarta. Entrepreneurship Orientation and Marketing Innovation have no effect on the Competitive Advantage of Culinary MSMEs in Jakarta. Competitive Advantage has a significant effect on the Business Performance of Culinary MSMEs in Jakarta, Competitive Advantage is not a good mediating variable, the Entrepreneurial Orientation and Marketing Innovation of Culinary MSME Business Performance variables in Jakarta.